2016
DOI: 10.3168/jds.2016-11014
|View full text |Cite
|
Sign up to set email alerts
|

Technical note: Validation of a commercial system for the continuous and automated monitoring of dairy cow activity

Abstract: Current farm sizes do not allow the precise identification and tracking of individual cows and their health and behavioral records. Currently, the application of information technology within intensive dairy farming takes a key role in proper routine management to improve animal welfare and to enhance the comfort of dairy cows. An existing application based on information technology is represented by the GEA CowView system (GEA Farm Technologies, Bönen, Germany). This system is able to detect and monitor anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…We developed a model to the measure the feeding behavior of dairy cows using UWB indoor positioning system with 97.6% accuracy compared to reference method Insentec feeders (RFID and photocell combination). The results are in agreement with those obtained previously by Tullo et al (2016) and Oberschätzl et al (2015). The use of Viterbi algorithm in addition to logistic regression clearly improved the model performance in calculating the duration and number of feeding bouts.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We developed a model to the measure the feeding behavior of dairy cows using UWB indoor positioning system with 97.6% accuracy compared to reference method Insentec feeders (RFID and photocell combination). The results are in agreement with those obtained previously by Tullo et al (2016) and Oberschätzl et al (2015). The use of Viterbi algorithm in addition to logistic regression clearly improved the model performance in calculating the duration and number of feeding bouts.…”
Section: Discussionsupporting
confidence: 94%
“…Ultra wide-band (UWB) based systems have an accuracy of below 1m in dairy barns after proper filtering (Pastell et al, 2018;Porto et al, 2014). These systems have been used to measure the feeding time of cows based on their proximity to feeding area (Shane et al, 2016;Tullo et al, 2016;Oberschätzl et al, 2015) as compared to behavioral observations. Other automatic on-farm options for monitoring feeding time include RFID based systems, accelerometers (Arcidiacono et al, 2017;Thorup et al, 2016) and computer vision (Porto et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A more detailed observation of the activity levels and behaviors of the cows in the collecting yards and in the parlor would be beneficial for future training and validation of algorithms for the classification of activities corresponding to being out of the pen for milking. However, it was not logistically possible in the current study to observe the activity of an entire milking group (n >120), rather than the small sample studies reported recently in other studies (n = 8 in Porto et al, 2014; n = 5 in Tullo et al, 2016) that use only position rather than actual behavior to validate activity. Nevertheless, there is no reason to believe that any misclassification of behavior by the decision tree algorithm would be more likely for either of the lame or nonlame groups of cows; hence, the main results of our study (where we highlight significant differences in feeding) are unlikely to be affected.…”
Section: Barker Et Almentioning
confidence: 85%
“…Although validated for use on farms (e.g., Tullo et al, 2016), very few studies have examined at the application of these systems in dairy management or combined RTLS location data with activity data recorded from accelerometers. Arcidiacono et al (2017) reported the potential for RTLS to detect estrus in dairy cows and suggested that other applications might include monitoring disease or verifying the welfare status of cows.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible to localise animals via ultra-wideband technology (e.g. CowView; GEA Farm technologies GmbH, Germany (Tullo et al, 2016)). In pasture based systems, the accurate measurement of the animal's position used to be limited to global position system (GPS) based tracking systems (Williams et al, 2016), but other approaches that are less burdensome on batteries are being developed (e.g.…”
Section: Animal Status and Behaviour Sensorsmentioning
confidence: 99%